Nanoparticle-embedded hydrogel synthesized electrodes for electrochemical oxidation of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS). (June 2022) - Hwang, Jae-Hoon; Li Sip, Yuen Yee; Kim, Keug Tae; Han, Gaehee; Rodriguez, Kelsey L.; Fox, David W.; Afrin, Sajia; Burnstine-Townley, Alex; Zhai, Lei; Lee, Woo Hyoung
Abstract: In this study, sliver (Ag) and gold (Au) nanoparticles (NPs) were embedded on poly (acrylic acid) (PAA)/poly (allylamine) hydrochloride (PAH) hydrogel fibers for improved electrochemical oxidation (EO) of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) removal. The NPs-loaded PAA/PAHs shows the better charge transport compared to the ceramic nanofiber membranes (CNM) electrodes. At 10 mA cm −2 of current density, the Ag-PAA/PAH electrodes showed a faster removal of PFAS compared to the Ag-CNM electrode probably due to large surface area-volume ratio and high porosity from the hydrogel. Among NPs-loaded PAA/PAH electrodes, the Ag/Au-PAA/PAH electrodes showed the highest removal of PFOA (72%) and PFOS (91%) in 2 h with the maximum removal rate of PFOA (0.0046 min −1 ) and PFOS (0.0093 min −1 ). The rapid PFOS removal is possibly due to the high activity of electron transfer with a higher redox potential of SO4 - than OH. The highly stable F − generation was obtained from each electrode during reproducibility (n = 3). The net energy consumption from Ag/Au–PAA/PAH electrode was 164.9 kWh m −3 for 72% PFOA removal and 90 kWh m −3 for 91% PFOS removal, respectively. The developed Au-PAA/PAH electrodes were applied to lake water samples and showed acceptable PFOS removal (65%) with relative standard deviations (RSD) of 10.2% (n = 3) at 10 mA cm −2 of current density. Overall, the NP-embedded hydrogel nanofibers were proven to be a promising sustainable catalyst for the electrochemical PFAS oxidation in water. Graphical abstract: Image 1 Highlights: NPs-embedded hydrogel nanofiber electrodes for PFAS removal were newly developed. Ag/Au-PAA/PAH electrodes showed the highest removal of PFOA (72%) and PFOS (91%). Faster PFOS removal compared to PFOA was observed for Au, Ag, and Ag/Au-PAA/PAH electrodes. The energy consumption of electrochemical PFAS removal was relatively low.